Da filologia para a onomástica: edição e estudo dos antropônimos de um livro de batismo do início do século XX - Oliveira, Eliene Pinto de (2022)
In this dissertation, we carried out a philological and lexicological study of a Baptism Book drafted, in 1931 in Freguesia da Gameleira community, where is located João Durval Carneiro district in Feira de Santana city. Thereby, for the execution of this work we relied on two major areas: Philology, in respect to the realization of facsimilar and semidiplomatic editions of the book and the survey of the extrinsic aspects of the book, for the realization we relied on the works of: Acioli (1994); Barreto (2020); Berwanger and Leal (2008); Cambraia (2005); Coutinho (1976); Elia (1979); Grésillon (2007); Megale and Cambraia (1999); Lose et al (2018); Lose (2017); Melo (1971); Queiroz (2006, 2007); Spaggiari and Perugi (2004) and Spina (1977). After we carried out the editions and the survey of the characteristics of the book, we selected the names of baptized ones to carry out the lexical study. For this, we resort to Lexicology, more precisely to Onomastics, which is dedicated to the study of names in general, and because it is a Baptism Book, we studied the anthroponyms, part of Onomastics that investigates the people’s names. We used as theoretical contribution for the lexical study the works of: Abbade (2006, 2011); Amaral (2011); Amaral and Seide (2020); Barbosa (1990); Biderman (1998, 2001); Carvalhinhos (2007); Correia (2017); Dick (1992); Isquerdo (2020); Krieger (2006); Oliveira and Isquerdo (1998); Orsi (2012); Seide (2013); Soledade (2019); Vieira (2001), Vilela (1995) and Xavier (2011), as well as the etymological dictionaries of Guérios (1973); Machado (2003) and Nascentes (1952). In view of this, the objectives of this dissertation were the realization of the aforementioned editions, the description and etymological analysis of the prenames of the baptized ones in that year. From the execution of these objectives, we contributed to the hypotheses that ancient writings are important to understand the history of a people and that the proper names can reflect the identity and consequently the culture of a civilization. Moreover, the etymological study contributes to understand the evidence of linguistic contact between different peoples in the formation of Brazilian Portuguese.